PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA REALITA DI KELAS II SDN 09 PENABAHAN - Ningsih, Sri Utami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem of this research is how to using the media reality in the weight measurement of learning can improve student learning outcomes second grade at elementary school 09 Penabahan District of Sanggau Ledo?